Preserving the image of the city through the conservation of shophouse buildings at Pekan Lama Kuala Selangor, Kuala Selangor / Afif Farhan Masdar - Afif Farhan, Masdar (2020)
The preservation of image of the city is one of the most important aspects of urban planning. This effort was made to preserve the image or state of the city in order to preserve its cultural significance. Most urban preservation processes involve efforts such as treatment under specific conditions including retention, restoration, reconstruction, redevelopment, and customization. In this regard, the Pekan Lama Kuala Selangor that can be considered as an old town has existed since the time of the Selangor sultanate since the 1780s. Architecturally, there are several buildings in the city that have heritage values that can be preserved and preserved including a shop house building. As such, the preservation and image of the city has a strong connection because through the preservation of improvements in the physicality of the city it is possible to make the image of a city stand out. Preliminary discovery in the city of Pekan Lama Kuala Selangor indicate that no effort has been made by the parties responsible for the preservation of several heritage buildings that can be maintained to shape the city image of Pekan Lama Kuala Selangor. Although, the Pekan Lama Kuala Selangor provides the image as a heritage city, but studies show that there is not one element that the city is trying to highlight to shape the image.